Metric driven mobility modeling in tactical networks. (April 2013) - Ray, Sucharita; La Porta, Thomas; Basu, Prithwish; Cao, Guohong; Shaffer, Scott; Dent, Dave
Mobility management is a key aspect of designing and evaluating protocols for Mobile Ad Hoc Networks (MANETs). The high mobility of nodes in a MANET constantly causes the network topology to change. Mobility patterns of nodes have a direct effect on fundamental network characteristics, such as path length, neighborhood size, and link stability. Consequently, the network performance is strongly affected by the nature of mobility patterns. While evaluating protocols for a specific MANET application, it becomes imperative to use a mobility model that is able to capture the movement of nodes in an accurate manner. The objective of this work is to produce mobility models that are able to describe tactical mobility in military applications of MANETs. We provide models of four tactical scenarios, show that these models are accurate compared to synthetic traces, and that when used to evaluate network protocols, they provide different conclusions than when using generic mobility models.